APPLICATION OF AUGMENTED REALITY (AR) MEDIA BASED ON LOCAL WISDOM TO IMPROVE DIGITAL LITERACY SKILLS IN SOCIAL SCIENCES LEARNING - Murdiyah Winarti; Acep Supriadi; Dahlena, Alni (SAHUR Journal, 2025)
The problem of low student motivation to learn is an educational problem currently faced by Indonesia, namely low quality in various educational institutions. School changes need to be made to improve the quality of education. Teachers at driving schools are required to be able to provide enjoyable learning for students in one direction but with a variety of encouraging activities. The aim of this research is to identify competencies for increasing digital literacy skills through local wisdom content in social studies learning. The research method used is a quantitative method with a quasi-experimental design. Data collection techniques were carried out through pretest and posttest, observation and documentation studies. The data analysis technique uses the Winistep Rasch model analysis. The results of this research show that there is a significant increase in data on the digital literacy of students who use Augmented Reality (AR) media. From these data it can be concluded that there is an increase in students' digital literacy using Augmented Reality (AR) media. It can be identified that the item mean correlation is 1.00 with a reliability percentage level of 0.77 so that from the standard item of 50 items it can be increased to be at a separation level of 1.64. -167. Therefore, learning social studies using Augmented Reality (AR) media based on local wisdom content can increase students' digital literacy.